Optimalisasi Kultur Cacing Sutra (Tubifex Sp.) Sebagai Pakan Alami Untuk Larva Ikan - Alfriend John Saotama Halawa; Rosmawati Gea; Cindy Ardita Telaumbanua; Enjel Delahowuhowu Telaumbanua; Rosevelt Cerdas Lase; Vebriman Jaya Halawa; Destriman Laoli (Jurnal Ilmu Pertanian dan Perikanan, 2025)
Silkworms (Tubifex sp.) are one of the leading natural feeds that are rich in protein, essential amino acids, and fats, and have a body size suitable for consumption by fish larvae. However, its limited availability and fluctuating quality are challenges in fish hatchery activities. This study aims to optimize the direct cultivation of silk worms in tarpaulin ponds with a field experiment approach, in order to increase the quantity as natural feed. The research was conducted at Ceria Group, Tugalagawu Village, Sirombu Sub-district, West Nias Regency, from May 27 to June 15, 2025. The methods used included the use of mud media enriched with organic materials such as bran and tofu pulp, and fermentation with EM4 to increase nutrient availability. Environmental parameters such as temperature (26-28°C) and pH (6.8-7.2) were controlled during the rearing period. The results showed that organic fermentation media was able to increase worm biomass to 80-120 g/m² with a harvest efficiency of 75%. The worms produced had visual quality and nutritional content suitable as larval feed, with potential protein content of 55-60% and fat content of 13-15%. This study concludes that local fermentation-based cultivation techniques can increase the efficiency of silk worm production while supporting natural food self-sufficiency at the coastal community level.